Long noncoding RNA as an indicator differentiating schizophrenia from major depressive disorder and generalized anxiety disorder in nonpsychiatric hospital. (March 2017) - Cui, Xuelian; Niu, Wei; Kong, Lingming; He, Mingjun; Jiang, Kunhong; Chen, Shengdong; Zhong, Aifang; Zhang, Qiaoli; Li, Wanshuai; Lu, Jim; Zhang, Liyi
Aim: Depression and anxiety are common symptoms for schizophrenia (SZ) in the early onset. This study aimed to determine whether long noncoding RNAs (lncRNAs) can be indicators for diagnosing SZ in nonpsychiatric hospitals.Materials & methods: Three upregulated SZ lncRNAs, six downregulated major depressive disorder (MDD) lncRNAs and three upregulated generalized anxiety disorder (GAD) lncRNAs were cross-validated in 45 SZ patients, 48 MDD patients, 52 GAD patients and 40 controls by reverse transcription-PCR.Results: Three SZ lncRNAs were significantly downregulated in GAD patients. The expression of the six MDD lncRNAs showed an opposite trend in SZ patients, and the three GAD lncRNAs also showed significant differences between SZ and GAD patients.Conclusion: The three upregulated SZ lncRNAs are not entirely replicated in MDD and GAD patients and could be potential indicators for distinguishing SZ from MDD and GAD in nonpsychiatric hospital.